Local government financing during the electoral business cycle: Analysing the role of intergovernmental political alignment on municipality budgets in Greece - Anastasios Kitsos; Antonios Proestakis (University of Birmingham, Birmingham Business School, 2018)
This paper examines the role of political alignment and the electoral business cycle on municipality revenues in Greece for the period 2003-2010. A panel dataset combining local and national elections with local budgets is used to run a fixed-effects econometric model. The findings suggest that municipalities which are politically aligned to the national government receive more funds in the runup to elections. This is evidence of electoral considerations in the allocation of resources and calls for policy changes promoting greater fiscal decentralisation to reduce pork-barrelling and rent-seeking, as well as the dependency between the local and national government levels.
Keywords: H50; H72; H77; R12; R58; 330; distributive politics; government grants; pork-barrel; clientelism; fiscal decentralisation; partisanship